Facilitators and barriers to participation of the private sector health facilities in health insurance & government-led schemes in India - Harsh S. Dave; Jay R. Patwa; Niraj B. Pandit (Elsevier, 2021)
Background: In India, policymakers are in an opined that expansion of public-funded health insurance is the key to achieve Universal Health Coverage (UHC). Despite untapped potential to be part of such government-run public-funded health scheme, many private service providers are reluctant to join in such scheme due to various reasons. This paper aims to evaluate facilitators, barriers and perception to participation of the private sector health facilities in Health Insurance & government-led schemes. Methods: Present study was conducted in 83 private hospitals of Vadodara city. Sampling frame was formed & with the use of random number table, 83 hospitals were selected randomly. Data collection was done in pre tested, pre formed questionnaire & respondents were the medical superintendent or the person in-charge of the hospital. Results: In the present study 30% & 26% of hospitals were enrolled for cashless private health insurance facility & government health schemes respectively. Social service, competition and increase clientele were the common reason sought for enrolment in government health schemes. Low & delayed reimbursement, bribe to clear payment, limited services covered, administrative issues were the common problems identified for non-enrolment. There was an association between a number of beds in the hospital & enrolment to government health scheme (p < 0.05). Availability of cashless private health insurance facility (p < 0.01) and satisfied with the current TPA model of health insurance (p < 0.05) were also found statistically significant. Conclusion: Timely & rational increase in remuneration, expanding the scope of services and use of appropriate technology for ease in administration is the need of an hour to engage vast service providers under the ambit of public-funded health insurance.